2016
DOI: 10.1126/sciimmunol.aag1266
|View full text |Cite
|
Sign up to set email alerts
|

The intersection of radiotherapy and immunotherapy: Mechanisms and clinical implications

Abstract: By inducing DNA damage, radiotherapy both reduces tumor burden and enhances anti-tumor immunity. Here, we will review the mechanisms by which radiation induces anti-tumor immune responses that can be augmented using immunotherapies to facilitate tumor regression. Radiotherapy increases inflammation in tumors by activating the NF-κB and the Type I interferon response pathways to induce expression of pro-inflammatory cytokines. This inflammation coupled with antigen release from irradiated cells facilitates dend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
125
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(125 citation statements)
references
References 106 publications
0
125
0
Order By: Relevance
“…RT‐induced DNA damage may generate neoantigens and augment the anti‐tumor immunity. Moreover, RT has the potential to increase the expression of cell surface receptors and tumor‐associated antigens . The combination of RT and ICI is based on the enhancing effect of RT on programmed death ligand 1 expression in the TME, which attenuates the sensitivity of anti‐tumor immune response .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RT‐induced DNA damage may generate neoantigens and augment the anti‐tumor immunity. Moreover, RT has the potential to increase the expression of cell surface receptors and tumor‐associated antigens . The combination of RT and ICI is based on the enhancing effect of RT on programmed death ligand 1 expression in the TME, which attenuates the sensitivity of anti‐tumor immune response .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, RT has the potential to increase the expression of cell surface receptors and tumor-associated antigens. 7,25,26 The combination of RT and ICI is based on the enhancing effect of RT on programmed death ligand 1 expression in the TME, which attenuates the sensitivity of anti-tumor immune response. 27 Moreover, Reits et al 28 reported that RT could upregulate the expression of major histocompatibility complex class I on the tumor cell surface to enhance presentation of tumor-specific peptides, increasing the effects of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…These effects may be especially relevant to high‐dose irradiation courses in comparison with more conventional courses and are the second major reason that SRS/SABR may be radiobiologically preferable to conventional treatments. A growing body of literature has also demonstrated that radiation can induce abscopal effects on distant, untreated sites of cancer and that this affect is associated with high‐dose irradiation and can be amplified by use of such therapies as immune checkpoint inhibitors and other immunomodulating drugs . This is an active area of clinical research as well …”
Section: Biological Principles Of Sabrmentioning
confidence: 99%
“…A growing body of literature has also demonstrated that radiation can induce abscopal effects on distant, untreated sites of cancer and that this affect is associated with high-dose irradiation and can be amplified by use of such therapies as immune checkpoint inhibitors and other immunomodulating drugs. (28,29) This is an active area of clinical research as well. (30)…”
Section: Biological Principles Of Sabrmentioning
confidence: 99%
“…The understanding gained from studying the interaction of the immune system and cancer can be used to design interventions that improve the immune response to cancer. While conventional cancer therapies have immunological effects [301,302] , here, three approaches to cancer immunotherapy will be discussed: therapeutic vaccination, checkpoint modulation, and adoptive cell transfer (ACT).…”
Section: Therapeutic Interventionsmentioning
confidence: 99%